The mindful law student : a mindfulness in law practice guide - Rogers, Scott L. (United Kingdom: Edward Elgar Publishing Limited, 2022)
'The Mindful Law Student is an innovative guide to learning about mindfulness and integrating mindfulness practices into the law school experience. Through the use of metaphor, insight, mindfulness practices, and relaxation and self-care exercises, students are reminded of the tools they have long carried with them to navigate the exciting and challenging environment of law school and the practice of law. Scott Rogers brings readers on a journey through the law school experience with seven hypothetical students who experience situations not unlike their own that make tangible the challenges, benefits, and promise of mindfulness. He provides real-world examples of applying mindfulness in law school using language of the law to impart mindfulness insights and practices. This novel guide is an approachable and valuable resource for any law student'--
Foreword / Rhonda V. Magee -- Part I: Mindfulness elements -- Leadership -- Attention -- Relaxation -- Awareness -- Mindfulness -- Part II: Mindfulness and you -- Solitude -- Connection -- Self-Care -- Movement -- Practice -- Part III: Mindfulness integrations -- Listening -- Negotiation -- Judgment -- Creativity -- Freedom -- The spiral exercise -- Practice journals.
Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ CIP/ Innowawasan
Includes bibliographical references and index.
Keywords: Law students -- United States -- Conduct of life; Mindfulness (Psychology); Law -- Study and teaching -- Psychological aspects; Practice of law -- Psychological aspects